QUIN 2.0 - new release of the QUaternary fault strain INdicators database from the Southern Apennines of Italy - Giusy Lavecchia; Simone Bello; Carlo Andrenacci; Daniele Cirillo; Federico Pietrolungo; Donato Talone; Federica Ferrarini; Rita de Nardis; Paolo Galli; Joanna Faure Walker; Claudia Sgambato; Marco Menichetti; et al. (Scientific Data, 2024)
Abstract QUIN database integrates and organizes structural-geological information from published and unpublished sources to constrain deformation in seismotectonic studies. The initial release, QUIN1.0, comprised 3,339 Fault Striation Pairs, mapped on 445 sites exposed along the Quaternary faults of central Italy. The present Data Descriptor introduces the QUIN 2.0 release, which includes 4,297 Fault Striation Pairs on 738 Structural Sites from southern Italy. The newly investigated faults span ~500 km along the Apennines chain, with strikes transitioning from ~SE to ~SW and comprehensively details Fault Striation Pairs’ location, attitude, kinematics, and deformation axes. Additionally, it offers a shapefile of the fault traces hosting the data. The QUIN 2.0 release offers a significant geographic extension to the QUIN 1.0, with comprehensive description of local geometric-kinematic complexities of the regional pattern. The QUIN data may be especially relevant for constraining intra-Apennine potential seismogenic deformation patterns, where earthquake data only offer scattered or incomplete information. QUIN’s data will support studies aimed at enhancing geological understanding, hazard assessment and comprehension of fault rupture propagation and barriers.